A future we can love : how we can reverse the climate crisis with the power of our hearts & minds : inspired by the conversation between his holiness The Dalai Lama & Greta Thunberg - Bauer-Wu, Susan; Higgs, Stephanie (Shambhala Publications, 2023)
"In early 2021, a humble, old Tibetan monk in maroon and yellow robes met with a slight young woman from Sweden. He is a survivor of violence and oppression whose radiant happiness and empathy have become world famous; she a fiery activist whose uncompromising clarity helped spark the global youth movement for climate action. When these two people-the Dalai Lama and Greta Thunberg-met and spoke for the first time, millions of people around the world took notice. The palpable sense of promise in their meeting drew its energy in part from the contrast of these two figures-one a scion of peace and patience, the other a rising symbol of the need for urgent action. Yet Greta and the Dalai Lama agree wholeheartedly that the climatic and ecological threats facing our planet require the attention and action of all human beings. "It is encouraging to see how you have opened the eyes of the world to the urgency to protect our planet, our only home," the Dalai Lama had written to Greta in a letter encouraging her to persevere. Though more and more people are alarmed by climate change, many of us remain stuck in inaction-paralyzed by difficult emotions like fear or grief, or simply uncertain what we can do. A Future We Can Love uses the inspiration of the Dalai Lama and Greta's words and life stories to embark on a four-part journey toward connection, hope, and purpose. The Buddhist concept of interdependence shows that even the most ominous aspects of climate change, such as the greenhouse gas feedback loops that are ever closer to spinning out of control, can be related to understandings familiar from our daily lives. And once that connection is made-once we see that the climate is our climate-then there is no turning back from our responsibility to act, which includes our responsibility to sustain our own spiritual and emotional well-being such that we can continue to act. Filled with the Dalai Lama's hard-earned wisdom, Greta's piercing focus, and dozens of accessible practices of climate activism and personal resilience, this book offers a path not just out of inaction but toward a future we can love. "Things may look dark, but I'm telling you, there is hope, and that hope comes from the people, from democracy, from you," says Greta. "We have passed a social tipping point, we can no longer look away from what our society has been ignoring for so long. It is an existential crisis. We must now do the seemingly impossible. And that is up to you and me. Because no one else will do it for us.""--